Analisis Aliran Udara dan Kenyamanan Termal di Laboratorium Perpindahan Panas dan Massa menggunakan Metode Computational Fluid Dynamics (CFD): Air circulation and Thermal Comfort Analysis of Heat & Mass Transfer Laboratory Using Computational Fluid Dynamics (CFD) Method - Jason Prathana Liawan; Harto Tanujaya; Steven Darmawan (Fakultas Teknik Universitas Pancasila, 2023)
Air circulation and thermal comfort are some of many factors that affects user’s behavior in indoor activity, particularly in learning activity. With appropriate air quality and thermal comfort, it is easier for students to focus on the learning process. In addition, better air circulation can also benefit to the health of the people inside the building, for instance, according to WHO (World Health Organization), appropriate airflow may reduce the spread of SARS-CoV-2 which lately has caused a COVID-19 pandemic. However, air circulation and distribution have not a concern yet due to existing room condition and advanced technology that is needed, in L 609 classroom and Heat & Mass Transfer Laboratory, in this research. CFD method implementation for this case is used to show existing air circulation condition and necessary recommendations to get better air circulation. CFD simulation is done 3 dimensionally with 44344 nodes tetrahedral mesh on 2 configuration room condition, which are classified based on air input from AC, door gap, and with or without window opening. Based on CFD simulation results, the 2nd configuration with window opening indicate the best configuration with air velocity around 0,8 m/s dan room temperature 295,8 – 302,1 K. With window opening, the air flow condition met the ANSI/ASHRAE 55 and hoped to reduce COVID-19 spreading.